Academic motivation of primary school pupils: Relation with general feelings towards school and specific aspects of the quality of school life - Marija Buterin Mičić (Christian Academic Circle, 2021)
The research presented in this paper is aimed towards examining the relation between the pupils’ perception of the school life quality and different types of academic motivation (external and autonomous). The data was collected using Self regulation questionnaire-Academic (Ryan & Connell, 1989) and Quality of school life questionnaire (Ainley & Bourke, 1982). The research included 434 primary school pupils from fifth to eighth grade. A positive correlation was found between all variables, where the strength of the correlation varies depending on type of academic motivation. In general, it can be concluded that those pupils who express more positive feelings towards school and who more assess specific aspects of school life more positively are more autonomously motivated to fulfill school obligations. Obtained results are discussed with reference to the relevance of pupils’ quality of school life in enhancing autonomous motivation in the academic domain.